Intellectual freedom: Waving and wavering across three national contexts. (October 2022) - Oltmann, Shannon M; Samek, Toni; Cooke, Louise
The 1999 IFLA Statement on Libraries and Intellectual Freedom makes no explicit distinction between personal and professional ethics, though there are implicit indications that there may be divergence between professional and personal considerations. Across three national contexts (the USA, Canada, and the UK), we explore the gaps between professional and personal ethics, as well as how these gaps have been potentially exploited, addressed, or resolved. There have been waves of debate about intellectual freedom and social responsibility across these three national contexts. In the contemporary age, we see clashes around conceptions of neoliberalism, neutrality, expressive freedom, justice, diversity, equity, inclusion, and anti-racism. The divergence of opinion comes from both the left and the right. The gap between library rhetoric and how it is practiced on the ground in different contexts is visibly shifting and under increased scrutiny, certainly in the USA, Canada, and the UK.